(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article highlights the importance of using technological terms in primary school technology lessons and their role in the educational process. The author provides recommendations on methods of explaining technological terms to students in a simple and understandable form, their assimilation through practical exercises, and increasing technological literacy. The article emphasizes that the use of terminology not only develops students’ knowledge and skills but also serves to increase their creative thinking and interest in technology. At the same time, the necessity of adapting technological terms to the age and psychological characteristics of children is indicated. The article presents the theoretical and practical foundations for the effective use of technologies in primary education.